Part 2: In vitro cytotoxicity studies of two ML 2 complexes (M = Pd, Pt; L = 2-cyano-2-isonitroso-N-morpholylacetamide, HMCO - Ratcliff, Jessica; Durham, Paul; Keck, Michael; Mokhir, Andriy; Gerasimchuk, Nikolay (Inorganica Chimica Acta, 2012)
In recent years, many non-classical groups of Pt-compounds, including complexes with the trans-geometry, polynuclear complexes, and compounds with a variety of extended heterocyclic ligands, were obtained and studied. Part 1 of this work contains the results of our X-ray crystallographic and computational studies of a group of recently-discovered cytotoxic Pd and Pt complexes of the new cyanoxime ligands HPipCO and HMCO. Here we present the results of our in vitro investigations of two M(MCO) (M = Pd, Pt) compounds against two morphologically different human cancer cell lines - epithelial cervical cancer HeLa cells, and WiDr solid tumor colon carcinoma. The Trypan Blue exclusion method was used for the assessment of the complexes' cytotoxicity. The data indicated a profound in vitro activity of new M(MCO) (M = Pd, Pt) complexes, comparable to that of cisplatin, which was used as a positive control. The palladium MCO complex was found to be consistently slightly more active than its corresponding Pt-analog. Binding of the above compounds to a variety of the DNA was studied by UV-Vis spectroscopy, gel electrophoresis, fluorescent intercalator displacement (FID) assay, and the mitochondria metabolism assay. No evidence of an interaction of either Pd(MCO) or Pt(MCO) complex with different types of DNA was found, which infers a mechanism of cytotoxicity of these new metallo-cyanoximates different from one of the cisplatin family. This immediately suggests different active species involved in the cellular interactions, as well as different metabolites. Consequently, it implies the absence of the negative side effects so common to the cisplatin family of anticancer drugs. © 2011 Elsevier B.V. All rights reserved.